Financiamiento empresarial y su influencia en el crecimiento de empresas comerciales de la provincia de Maynas año 2025 - Mozombite Taricuarima, Mario (2025)
The limited access to financing for micro and small enterprises (MSEs) in the province of Maynas, Peru, is due to factors such as informality and lack of credit history, among others, which hinders their growth and competitiveness. Therefore, this research determines how business financing influences economic, market, and organizational growth in commercial companies in the province of Maynas in 2025. Using a quantitative, observational approach and a non-experimental study at the causal level, through the use of linear regression models and descriptive statistical analysis, it was found that business financing exerts a significant and positive influence on the three dimensions of growth, with a greater impact on economic (R² = 0.315) and market (R² = 0.272) growth, and a more limited influence on organizational growth (R² = 0.115). The descriptive results show a favorable perception of both financing and growth, although gaps are identified in credit management and the strategic use of financial resources. It is concluded that financing, while a key factor for business development, requires complementary policies such as training, technical support, and adaptation of financial products to local circumstances. In summary, the need to integrate access to credit with efficient management is highlighted in order to achieve sustainable and equitable business growth in the province of Maynas. This coordination is essential to boost the regional economy and improve business competitiveness.